Therapeutic drug monitoring of thiopurines: Effect of reduced 6‐thioguanine nucleotide target levels in inflammatory bowel disease patients. Issue 8 (29th March 2022) - Boekema, Monique; Horjus – Talabur Horje, Carmen S.; Roosenboom, Britt; Roovers, Lian; van Luin, Matthijs
Abstract : Aims: The effect of the Dutch nationwide adjustment of reducing 6‐thioguanine nucleotide (6‐TGN) target values (from 600–1200 to 320–630 pmol/8 × 10 8 red blood cells [RBC]) on toxicity and clinical outcome of thiopurine treatment in patients with inflammatory bowel disease has not yet been established. Therefore, the authors determined the incidence of toxicity‐induced discontinuations and efficacy at both target concentrations. Methods: This retrospective study was performed in inflammatory bowel disease patients treated with azathioprine or mercaptopurine. Two groups were defined: the former target (FT) group with target concentrations of 600–1200 pmol/8 × 10 8 RBC and the adjusted target (AT) group with target concentrations of 320–630 pmol/8 × 10 8 RBC. Patients were followed for maximum 52 weeks or until discontinuation of thiopurine therapy. Data were collected from the local hospital electronic health software of Rijnstate Hospital. Results: In total, 151 patients were included, 76 in the FT group and 75 in the AT group. At week 52, 100 out of 151 patients (66%) of the total population discontinued thiopurine therapy. Forty‐eight of the discontinuations were due toxicity (48%). The incidence of toxicity induced discontinuations was 35% in the AT group vs . 47% in the FT group ( P  = .25). No loss of efficacy was seen in the AT group. Conclusion: After reduction of the target range, there was a trend towards fewer toxicity‐induced discontinuations, albeit not statistically significant. In addition, this study did not find any indication that the reduction of the target range diminished efficacy.